Students’ Perceptions on Reflective Journal as Self-Assessment to promote writing skills in EFL Class - Sumardi Sumardi; Sri Samiati Tarjana; Hanna Novariana Azizah Ni'ma (Hasanuddin University, 2019)
The purpose of this study was to examine students’ perspectives on best practices to promote writing skills by using self-assessment technique named reflective journal in EFL class. The method of this study is qualitative research. The data collected and analyzed from this study to compromise a better understanding of students’ perspectives on how reflective journal writing of self-assessment promotes their writing proficiency. In this study, the writer collected the data by using semi-structured interviews and focused on twelve students from high school who taught by using reflective journal in Surakarta, Jawa Tengah. The finding of this study identified how students’ perspectives on reflective journals to promote their writing proficiency. The result of this study indicated the positive impacts of reflective journals in enhancing students’ writing proficiency. Nevertheless, there were several difficulties students faced during learning process. There were also some challenges such as students’ lack of motivation. However, both the teacher and the students were actively involved in overcoming those problems. In sum, students thought that reflective journal makes their writing practices exciting, enjoying, and motivating.